2005
DOI: 10.1086/431222
|View full text |Cite
|
Sign up to set email alerts
|

TheGALEXUltraviolet Variability Catalog

Abstract: We present version 1.0 of the NASA Galaxy Evolution Explorer (GALEX ) ultraviolet variability (GUVV) catalog, which contains information on 84 time-variable and transient sources gained with simultaneous near-ultraviolet (NUV) and far-ultraviolet (FUV) photometric observations. These time-variable sources were serendipitously revealed in the various 1N2 diameter star fields currently being surveyed by the GALEX satellite in two ultraviolet bands (NUV 1750-2750 8, FUV 1350-1750 8) with limiting AB magnitudes of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 10 publications
1
34
0
Order By: Relevance
“…Neither category is unexpected given that our search is based on consecutive g P1 r P1 detections with a time-span of about 0.5 hr. M dwarf flares typically exhibit blue colors indicative of T ∼ 10 4 K, with timescales of minutes to hours, and are thus ubiquitous in searches that utilize rapid observations in the ultraviolet (Welsh et al 2005(Welsh et al , 2006 or blue optical bands (Becker et al 2004;Kulkarni & Rau 2006;Rau et al 2008). Similarly, our requirement of two consecutive detections within ∼ 0.5 hr, with non-detections on preceding or subsequent nights is effective at capturing asteroids near the stationary point of their orbits (i.e., at solar elongations of about 130 deg for main-belt asteroids).…”
Section: Limits On the Rate Of Extragalactic Fastmentioning
confidence: 99%
“…Neither category is unexpected given that our search is based on consecutive g P1 r P1 detections with a time-span of about 0.5 hr. M dwarf flares typically exhibit blue colors indicative of T ∼ 10 4 K, with timescales of minutes to hours, and are thus ubiquitous in searches that utilize rapid observations in the ultraviolet (Welsh et al 2005(Welsh et al , 2006 or blue optical bands (Becker et al 2004;Kulkarni & Rau 2006;Rau et al 2008). Similarly, our requirement of two consecutive detections within ∼ 0.5 hr, with non-detections on preceding or subsequent nights is effective at capturing asteroids near the stationary point of their orbits (i.e., at solar elongations of about 130 deg for main-belt asteroids).…”
Section: Limits On the Rate Of Extragalactic Fastmentioning
confidence: 99%
“…Active galactic nuclei (AGN) and quasars demonstrate stronger variability with decreasing wavelength and longer timescales of years (Vanden Berk et al 2004). UV variability studies of GALEX data observed as part of the All-Sky, Medium, and Deep Imaging baseline mission surveys (AIS, MIS, DIS) from 2003 to 2007, yielded the detection of M-dwarf flare stars (Welsh et al 2007), RR Lyrae stars, AGN, and quasars (Welsh et al 2005;Wheatley et al 2008;Welsh et al 2011), and flares from the tidal disruption of stars around dormant supermassive black holes (Gezari et al 2006(Gezari et al , 2008a(Gezari et al , 2009. Serendipitous overlap of 4 GALEX DIS fields with the optical CFHT Supernova Legacy Survey, enabled the extraction of simultaneous optical light curves from image differencing for 2 of the tidal disruption event (TDE) candidates (Gezari et al 2008a), and enabled the association of transient UV emission with two Type IIP supernovae (SNe) within hours of shock breakout (Schawinski et al 2008;Gezari et al 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, if a flare is observed by TAUVEX, the comparison of the theoretical flux ratios with the measured ones can help in determining the value of the plasma electron density during the flare event, in the assumption that the increase in electron pressure during the flare has a major influence on the ratios (Welsh et al 2006). In addition, since GALEX has produced a catalog of GALEX transient events (Welsh et al 2005), the predictions for the stellar-planetary collision UV flashes could be tested against the existing GALEX data set, and this topic will also be addressed in the forthcoming paper.…”
Section: Resultsmentioning
confidence: 99%